Implementasi Metode Waterfall Pada Aplikasi Inventory Barang Berbasis Web - Supriatiningsih, Supriatiningsih (Informatics and Computer Engineering Journal, 2023)
Goods Inventory is the management of inventory of goods, both consumable and non-consumable goods, which are needed to support operational activities. Companies sometimes have difficulty managing inventory, while the management system still applies manual systems such as recording goods in and out, borrowing goods which is less controlled. For this reason, a website-based inventory information system was created using the waterfall method in which there are several stages, namely analysis of software requirements, design, creation of program code, testing and support or maintenance to help manage inventory and asset borrowing. Meanwhile, for data modeling, a structured method is used, namely Entity Relationship Diagram (ERD) to describe the data model and Logical Record Structure (LRS) to make it easier to define file specifications. This information system application regarding employee recruitment is a solution for disseminating information about employee recruitment and selection online and can assist managers in managing data and transactions in and out of goods